BiVO4 Photoanodes for TEMPO‐Mediated Benzyl Alcohol Oxidation in Organic Media. Issue 10 (29th August 2022) - Klinova McMillan, Nelli; Lopez, Diego A.; Leem, Gyu; Sherman, Benjamin D.
Abstract: The photoelectrochemical production of fuels, exemplified by light‐driven water splitting to hydrogen and oxygen, offers a sustainable option to offset dependence on fossil fuels. A low‐cost, efficient, and stable photoelectrochemical approach to solar fuels remains elusive but using similar materials and photoelectrodes for chemical production or biomass conversion offers an appealing alternative. This work reports a facile method for fabricating pristine (undoped) BiVO4 photoanodes to carry out TEMPO‐mediated benzyl alcohol oxidation to benzaldehyde in organic media (TEMPO=2, 2, 6, 6‐tetramethylpiperidinyl‐N‐oxyl). The best performing BiVO4 photoanode studied here gave a faradaic efficiency (FE) of 85±5% for benzaldehyde formation in the presence of TEMPO and pyridine during a 2.5‐hour reaction. Compared with direct electrocatalytic conversion under the same conditions, light capture and conversion by the BiVO4 surface decreased the required applied bias by 46 %. To our knowledge, this is the first report of visible light assisted, TEMPO‐mediated benzyl alcohol oxidation using pristine BiVO4 photoanodes in organic media. Abstract : The use of pristine (undoped) BiVO4 photoanodes to drive TEMPO‐mediated benzaldehyde production from benzyl alcohol in organic media is reported in this work. High observed faradaic efficiencies (85±5%) show the promise of this renewable photo‐assisted approach to chemical production and processing.